The image of the library and information profession : how we see ourselves : an investigation : a report of an empirical study undertaken on behalf of IFLA's Round Table for the Management of Library Associations - Prins, Hans.; Gier, Wilco de.; Bowden, Russell; Round Table for the Management of Library Associations (München ; New Providence [N.J.] : K.G. Saur, 1995)
This report is a empirical study that explains how human see themselves: an investigation : a report of an empirical study undertaken on behalf of IFLA's Round Table for the Management of Library Associations
Includes bibliographical references.
ijb, 15/01/2019
Loans
Keywords: Librarians; Librarians; Libraries and society